The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/252593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Normative age modelling of cortical thickness in autistic males

Abstract: Understanding heterogeneity in neural phenotypes is an important goal on the path to precision medicine for autism spectrum disorders (ASD). Age is a critically important variable in normal structural brain development and examining structural features with respect to age-related norms could help to explain ASD heterogeneity in neural phenotypes. Here we examined how cortical thickness (CT) in ASD can be parameterized as an individualized metric of deviance relative to typically-developing (TD) age-related nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…While many other neuroimaging studies of ASD have reported greater cortical thickness values 5,15,31 , others have reported lower thickness 65 , or no differences 9 . Our findings of greater CT in ASD are largely in agreement with other large-scale neuroimaging studies, including studies using the ABIDE dataset 5,15,16,66 and recent findings by the ENIGMA consortium 6 . However, the recent ENIGMA study, in addition to greater CT in ASD in the frontal and posterior cingulate cortices, also reports significantly less CT in ASD in the temporal and parahippocampal cortices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While many other neuroimaging studies of ASD have reported greater cortical thickness values 5,15,31 , others have reported lower thickness 65 , or no differences 9 . Our findings of greater CT in ASD are largely in agreement with other large-scale neuroimaging studies, including studies using the ABIDE dataset 5,15,16,66 and recent findings by the ENIGMA consortium 6 . However, the recent ENIGMA study, in addition to greater CT in ASD in the frontal and posterior cingulate cortices, also reports significantly less CT in ASD in the temporal and parahippocampal cortices.…”
Section: Discussionsupporting
confidence: 91%
“…Results of studies examining different age ranges of ASD, in particular in those with small sample sizes, are often conflicting or inconsistent. Recent large scale studies examining wide age ranges that have attempted to reconcile these inconsistencies have reported cortical thickness differences in childhood and early adolescence, followed by normalisation of group differences later in life 5,6,66 . While we cannot strictly make inferences about cortical development from our cross-sectional dataset, here, we seem to recapitulate these results to an extent, though the results observed in our age-centred analysis are subtle.…”
Section: Discussionmentioning
confidence: 99%
“…Regression, a developmental feature seen in autistic individuals, is another key stratifier that is surprisingly under-studied but with plausible unique biological bases [95,96]. Within the developmental dimension, heterogeneity can be assessed as both inter-and intra-individual variability, but can also cover individualized deviance from group trajectories over time- [38] or age-specific norms [97,98]. Chronogeneity thus offers a unique vantage point on multi-level heterogeneity not covered by understanding heterogeneity at static time points.…”
Section: Approaches To Decomposing Heterogeneity In Autism: Top-downmentioning
confidence: 99%
“…The deviating participants were in many cases quite extreme, which suggests a possible reason for inconsistencies in case-control studies (Bethlehem et al, 2018). Therefore, the description of patients on the group level is certainly not sufficient, a cluster level description may not be refined enough to capture the complexity of ASD, which may, in fact, be relatively patient specific.…”
Section: The Future Of Pattern Classification and Stratification In Amentioning
confidence: 99%